The Effect of Financial Decisions on Equity Risk in Constructs Firms Listed on the Indonesian Stock Exchange - Tika, Tika Misla Wahyuni; Rasyid, Rosyeni (Financial Management Studies, 2024)
This study was conducted to determine the effect of financial decisions on equity risk in constructs firms listed on the Indonesia Stock Exchange with firm size and revenue growth as control variables. The population in this study were all firms in the constructs sector listed on the Indonesia Stock Exchange for the 2020-2022 period. Meanwhile, the sample in this study was determined using a purposive sampling technique, resulting in 19 samples and 57 total observation data. This study uses secondary data obtained from the official website of the Indonesia Stock Exchange and the firm's official website. The data analysis method used is panel data regression analysis using the Eviews 12 analysis tool. The results of the data analysis show that (1) Investment Decisions have no effect on Equity Risk (2) Funding Decisions have no effect on Equity Risk (3) Working capital decisions significantly and favorably impact equity risk.